Detection and phylogenetic analysis of Torque Teno Virus in blood samples of healthy individuals - Jarkasi, Nur Syazwani (2019)
Torque Teno Virus (TTV) is a single-stranded DNA virus which infects human population worldwide. TTV is characterized by exhibiting a vast genetic diversity generating a large number of variants that clustered into seven genetic lineages. High TTV prevalence was reported from several parts of Asian continent. However, there is a lack of information regarding TTV prevalence among healthy Malaysian population as well as its genetic diversity. In order to elucidate the prevalence of TTV in Malaysia, DNA extracted from 137 plasma samples of healthy individuals were screened for the presence of TTV DNA by PCR based on primers derived from different genomic regions (5´ UTR, 3´ UTR and N22). By using 5' UTR-derived primer, 70.80% of our studied population shows positive for TTV. For 3' UTR-derived primer, the result shows that 37.23% of the studied population positive for TTV. Meanwhile, 15.46% of TTV strains detected from 5´ UTR PCR is positive for N22 PCR. Phylogenetic analysis based on 3´ UTR region reveals that Malaysian isolates are clustered into four groups supported by high bootstrap value (89% to 100%). Pairwise genetic distance of 3' UTR region of Malaysian isolates shows small genetic distance range between 0.020 to 0.269 among them. Subsequently, one sample was selected for near full-length amplification. A total of 3349 bp TTV DNA was amplified, and the amplicon was cloned, sequenced and subjected to bioinformatic analysis. From the analysis, a new isolate of TTV, named TTVMY01, was identified. Phylogenetic analysis based on whole sequence and each region thereof revealed that TTVMY01 is clustered into genogroup 3a. From 29 TTV species, TTVMY01 exhibit smallest genetic distance with SANBAN species, a Japanese isolate. Several protein motifs identified in each predicted protein of SANBAN remain conserved in TTVMY01. With regards to 5´ UTR, this study demonstrates high frequency of TTV viremia among healthy Malaysian population, and in accordance with the reports from other geographical regions. Identification of new TTV variant may provide additional information for its genetic diversity, and it should be taken into consideration for pathogenicity study in the future.